The antiinflammatory sesquiterpene lactone parthenolide inhibits NF-κB by targeting the IκB kinase complex - Hehner, Steffen Peter; Hofmann, Thomas G.; Dröge, Wulf (The journal of immunology, 1999)
The transcription factor NF-κB is a key regulator of the cellular inflammatory and immune response. Therefore, components of the NF-κB-activating signaling pathways are frequent targets for antiinflammatory agents. This study shows that the sesquiterpene lactone parthenolide inhibits a common step in NF-κB activation by preventing the TNF-α-induced induction of IκB kinase (IKK) and IKKβ, without affecting the activation of p38 and c-Jun N-terminal kinase. Parthenolide impairs NF-κB-dependent transcription triggered by expression of TNFR-associated factor-2, mitogen-activated protein kinase/extracellular signal-regulated kinase kinase (MEKK1), and NF-κB-inducing kinase. This compound also prevents activation of both IKKs and DNA binding of NF-κB induced by MEKK and NF-κB-inducing kinase. Parthenolide targets a component of the IκB kinase complex without directly inhibiting IKKα, IKKβ, or MEKK1. Therefore, this sesquiterpene lactone could serve as a lead compound for the development of antiinflammatory remedies and is suitable as a molecular tool, allowing the dissection of TNF-α-derived signaling pathways leading to the activation of NF-κB, c-Jun N-terminal kinase, and p38.
Gesehen am 03.02.2021